2022
DOI: 10.1039/d2ob01792j
|View full text |Cite
|
Sign up to set email alerts
|

BiCl3 catalyzed synthesis of 2-amino-1,4-naphthoquinones and 1,4-naphthoquinon-2-sulfides and one-pot sequential amine-arylation of 1,4-naphthoquinone

Abstract: Using the Lewis acid catalyst BiCl3, a new method for the synthesis of 2-amino-1,4-naphthoquinones and 1,4-naphthoquinon-2-sulfides from 1,4-naphthoquinone has been devised. This method has a broad substrate range and easy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…The results revealed that use of KOH as the base resulted in a yield of 73 % for the target product 4 a and with the greatest increase in yield. After determining the optimal base, different copper and iron catalysts were further assessed, but no higher yield was observed than CuCl (entries [13][14][15][16][17]. In further studies, when the amount CuCl was increased to 15 mol%, the yield of 4 a was improved to 89 % (entry 18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that use of KOH as the base resulted in a yield of 73 % for the target product 4 a and with the greatest increase in yield. After determining the optimal base, different copper and iron catalysts were further assessed, but no higher yield was observed than CuCl (entries [13][14][15][16][17]. In further studies, when the amount CuCl was increased to 15 mol%, the yield of 4 a was improved to 89 % (entry 18).…”
Section: Resultsmentioning
confidence: 99%
“…[13] In 2022, Baishya et al developed a BiCl 3 catalyzed one-pot sequential amine-arylation of 1,4-naphthoquinone. [14] On the other hand, due to the interesting physicochemical properties, phosphorus-containing groups are one of the most valuable kinds of structural skeletons in synthetic, pharmaceutical chemistry, and materials science. [15] Substantial efforts have been devoted to incorporating phosphorus substituents into various valuable organic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Pure red color AQNQ was obtained by employing silicagel-filled column chromatography in a DCM−hexane (5:1 v/v) eluent system (yield = 80%). R f = 0.13 (SiO 2 ; CH 2 Cl 2 /hexane), mp = 209.1 °C (literature: 76 Synthesis of AQNQ−Cu Complex. To a solution of 20.0 mg (0.067 mmol) of the AQNQ compound dissolved in 6.0 mL ethanol at 76 °C, 41.4 mg (0.14 mmol) of Cu(NO 3 ) 2 was added.…”
Section: Synthesis Of Aqnqmentioning
confidence: 99%
“…Pure red color AQNQ was obtained by employing silica-gel-filled column chromatography in a DCM–hexane (5:1 v/v) eluent system (yield = 80%). R f = 0.13 (SiO 2 ; CH 2 Cl 2 /hexane), mp = 209.1 °C (literature: 210.4–210.8 °C). The 1 H NMR (500 MHz, in DMSO- d 6 ): δ = 10.27 (s, 1H, N–H), 9.00 (dd, 1H, Ar–H), 8.47 (dd, 1H, Ar–H), 8.11 (d, 1H, Ar–H), 8.00 (d, 1H, Ar–H), 7.83–7.89 (m, 3H, AR-H), 7.65–7.74 (m, 3H, Ar–H), 6.76 (s, 1H, Ar–H); the 13 C NMR (125 MHz, in DMSO- d 6 ): δ = 183.67 (CO), 181.99 (CO), 149.86,143.00, 139.68, 137.33, 135.58, 134.45, 133.45, 132.90, 130.68, 128.67, 127.70, 126.92, 125.94, 123.16, 122.83, 116.19, 105.49; IR (ATR): υ max /(cm –1 ) = 3226, 1670, 1633, 1604, 1592, 1571, 1531, 1490, 1463, 1432, 1380, 1344, 1332, 1294, 1261, 1243, 1162, 1126, 1092, 1068, 975; MALDI–TOF–MS: anal.…”
Section: Experimental Sectionmentioning
confidence: 99%